Prevalence of cholelithiasis in lion tamarins (Leontopithecus spp.) kept under human care by using abdominal ultrasound - Felippi, Daniel Angelo [UNESP]; Franco, Paolla Nicole [UNESP]; Bonatelli, Shayra Peruch [UNESP]; Silva, Jeana Pereira da [UNESP]; Guimaraes, Victor Yunes [UNESP]; Breda, Maria Rosa Santos [UNESP]; Pagani, Rafael; Santos, Bruna dos; Takahira, Regina Kiomi [UNESP]; Rahal, Sheila Canevese [UNESP]; Mamprim, Maria Jaqueline [UNESP] (Wiley-Blackwell, 2022)
Background: Cholelithiasis is a digestive system disorder of multifactorial origin that occurs due to stones formed in the gallbladder. This study aimed at investigating by abdominal ultrasound examination the prevalence of cholelithiasis in lion tamarins kept under human care. Methods: Thirty lion tamarins from five Brazilian zoos, including 17 golden lion tamarins and 13 golden-headed lion tamarins, were evaluated. Results: Considering all lion tamarins, the overall frequency of cholelithiasis was 53.3% (16/30). There were no significant differences between species and sex. Cholelithiasis was predominant (75.0%) in lion tamarins older than 5 years. Septate gallbladder was observed in 86.6% (26/30) of the lion tamarins. Of these, 53.8% (14/26) had gallstones. Biochemical analysis revealed a moderate positive correlation between gamma-glutamyl transferase and the number of gallstones. Conclusions: Asymptomatic cholelithiasis is frequent in lion tamarins kept under human care. Therefore, systematic monitoring through ultrasound should be part of the preventive care of these animals.
Keywords: Callitrichids; Ex situ; Gallstones; Septate gallbladder